2016
DOI: 10.1007/s13246-016-0422-5
|View full text |Cite
|
Sign up to set email alerts
|

Verification of absorbed dose using diodes in cobalt-60 radiation therapy

Abstract: The objective of this work was to enhance the quality and safety of dose delivery in the practice of radiation oncology. To achieve this goal, the absorbed dose verification program was initiated by using the diode in vivo dosimetry (IVD) system (for entrance and exit). This practice was implemented at BINO, Bahawalpur, Pakistan. Diodes were calibrated for making absorbed dose measurements. Various correction factors (SSD, dose non-linearity, field size, angle of incidence, and wedge) were determined for diode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Traditionally, TLDs and diodes have been the choice for use as an in vivo dosimeter due to their high accuracy in entrance dose determinations [76][77][78][79][80][81]. Evwierhurhoma, Ibitoye [76] determined the role of TLDs during in vivo dosimetry.…”
Section: Entrance Dose Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, TLDs and diodes have been the choice for use as an in vivo dosimeter due to their high accuracy in entrance dose determinations [76][77][78][79][80][81]. Evwierhurhoma, Ibitoye [76] determined the role of TLDs during in vivo dosimetry.…”
Section: Entrance Dose Assessmentmentioning
confidence: 99%
“…They showed that no significant difference existed between the prescribed dose and measured dose of the breast with a percentage deviation difference of less than 5%. Gadhi, Fatmi [81] developed an absorbed dose verification program using the diode in vivo dosimetry system for entrance dose measurements. Phantom studies carried out in their work showed that the percentage difference between measured and calculated dose for entrance setting remained within ±2%.…”
Section: Entrance Dose Assessmentmentioning
confidence: 99%